HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR MAHASISWA PGSD SEMESTER III UNIVERSITAS KARIMUN PADA MATA KULIAH STRATEGI PEMBELAJARAN SD - Desi Indriyani; Fitria Meilina; Tisrin Maulina Dewi (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This research is motivated by the different levels of motivation of the third semester PGSD students in the Elementary School Learning Strategy course. There are still students who pay less attention during group discussions, talking to friends, looking for other activities during learning and so on. The formulation of the problem in this study is whether there is a positive and significant relationship between learning motivation and learning outcomes of PGSD Semester III students at Karimun University in the SD learning strategy course. This study aims to determine whether there is a positive and significant relationship between learning motivation and learning outcomes of PGSD Semester III students at Karimun University in the SD learning strategy course. This type of research is correlational research. The population in this study were all third semester students of PGSD. The data collection technique used in this research is using observation and questionnaires (questionnaire). The results showed that there was a significant relationship between learning motivation and learning outcomes of PGSD Semester III students at Karimun University in the SD learning strategy course. Because the correlation coefficient is 0.619 > r table 0.3202, the calculation uses product moment correlation analysis, and the significance price is 0.000 <0.05. From the results of the correlation calculation, it is obtained that r count is 0.619 which indicates there is a moderate relationship between learning motivation and learning outcomes of PGSD Semester III students at Karimun University in the SD learning strategy course.